Pleasure, mind, and soul - Taylor, C.C.W. (Oxford University Press, 2008)
C.C.W. Taylor presents a selection of his essays in ancient philosophy, drawn from forty years of writings on the subject. The central theme of the volume is the moral psychology of Plato and Aristotle, with a special focus on pleasure and related concepts, an area central to Greek ethical thought. Taylor also discusses Socrates and the Greek atomists (including the Epicureans), showing how Plato's ethics grows out of the thought of Socrates, and that pleasure is also a central concept for the atomists. Pleasure, Mind, and Soul provides a fascinating survey of a range of important topics in the work of some of the greatest ancient philosophers, and which remain the subject of lively philosophical debate today